2020
DOI: 10.3389/fpsyt.2020.00722
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Remediation Interventions in Autism Spectrum Condition: A Systematic Review

Abstract: Background: Autism spectrum condition (ASC) is a lifelong neurodevelopmental condition characterized by difficulties in social cognition and heterogeneity of executive function which are suggested to be underpinned by neurobiological, prenatal and genetic factors. Cognitive remediation (CR) interventions are frequently used to address cognitive characteristics and improve cognitive and general functioning. However, the evidence is limited for ASC. This systematic review is the first to provide a narrative synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 86 publications
(153 reference statements)
0
27
0
Order By: Relevance
“…Furthermore, our findings highlight the potential value of other treatment options, such as DBT ( Linehan, 1993 ). Other therapeutic approaches are being trialled for autistic individuals with AN, such as Cognitive Remediation Therapy which aims to address specific cognitive difficulties, rather than directly addressing the ED ( Dandil et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings highlight the potential value of other treatment options, such as DBT ( Linehan, 1993 ). Other therapeutic approaches are being trialled for autistic individuals with AN, such as Cognitive Remediation Therapy which aims to address specific cognitive difficulties, rather than directly addressing the ED ( Dandil et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of males in research samples may induce gender-related biases affecting the development of psychosocial interventions ( 18 ). Two recent systematic reviews have reported a large predominance of males in studies on cognitive remediation or social skills training [up to 100% in some studies ( 8 , 19 )]. Similar proportions have been reported in studies targeting social skills in dating contexts ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The action plan can include strengthbased case management, improvements in physical and mental health, peer support interventions, joint crisis plans, cognitive remediation (CR), cognitive behavior therapy (CBT), social skills training (SST), self-stigma reduction, family support, and supported housing and supported employment (SE) (6,7). Psychiatric rehabilitation interventions have shown small to moderate effectiveness in improving patients'outcomes in adults with ASD (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that this particular form of therapy can be beneficial in improving cognitive flexibility, social cognition, and the heterogeneity of executive function, even clinical symptoms and working memory in autistic children as one study, including children and adolescent (age 6–21), established ( 55 ). On the other side, due to some methodological limitations of the studies conducted, it poses a question of generalizability of the submitted results ( 18 ).…”
Section: Cognitive Remediation Therapymentioning
confidence: 99%
“…One target of research concerning the cognitive aspect in individuals with ASD and AN over the last years is cognitive remediation therapy (CRT) ( 17 , 18 ). The assumption is that improving the cognitive function of the individual might enhance the ability to manage daily life tasks.…”
Section: Introductionmentioning
confidence: 99%